Integration of Person-Centered Counseling with Turangga Yaksa Dance Values to Develop Adolescents’ Self-Concept - Awalya Siska Pratiwi; Achmad Miftachul ‘Ilmi; Arbin Janu Setiyowati; Mariah Binti Kamaruddin (Program Studi BKPI IAIN Salatiga, 2022)
Culture is a pivotal aspect determining the success of the counseling process. Students in Senior High School 1 Karangan Trenggalek experience various self-concept-related problems. In this regard, Trenggalek Regency' Jaranan Turangga Yaksa emerges as one of the local cultural values potentially improving self-concept and development. In the counseling context, the person-centered counseling approach is typically employed to help the clients find their self-concept. The purposes of this study are threefold: (1) to describe the concept of person-centered counseling; (2) to describe the cultural values in the Jaranan Turangga Yaksa; (3) To integrate the values in Jaranan Turangga Yaksa with person-centered counseling approach to help adolescents develop self-concept. To this end, a five-stage literature review was conducted. It consisted of (1) literature collection, (2) literature selection; (3) reviewing literature sources; (4) concluding study results; and (5) discussing study results. Fifteen articles were reviewed. The values in the Jaranan Turangga Yaksa included religiosity, nationalism, independence, cooperation, and integrity. These values align with the person-centered counseling approach, which focuses on developing self-concept. This study concluded that the integration of person-centered counseling might help adolescents find their self-concept. This study is expected to be useful for counselors and other researchers in developing the concept of person-centered counseling with the values of the Jaranan Turangga Yaksa.